2011
DOI: 10.1002/lsm.21112
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy (PDT) using HPPH for the treatment of precancerous lesions associated with barrett's esophagus

Abstract: Background and Objectives Photodynamic therapy (PDT) with porfimer sodium, FDA approved to treat premalignant lesions in Barrett’s esophagus, causes photosensitivity for 6-8 weeks. HPPH (2-[1-hexyloxyethyl]-2-devinyl pyropheophorbide-a) shows minimal photosensitization of short duration and promising efficacy in preclinical studies. Here we explore toxicity and optimal drug and light dose with endoscopic HPPH-PDT. We also want to know the efficacy of one time treatment with HPPH-PDT. Study Design/Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
1
41
0
1
Order By: Relevance
“…[1][2][3] With high tumor avidity, the chlorin-based compound 2-(1-hexyloxyethyl)-2-devinyl pyropheophorbide-a (HPPH) has been shown to be a potential photosenstizer for imaging and treatment. 4 Recent HPPH-oriented laboratory research and early-phase clinical studies at Roswell Park Cancer Institute (RPCI) have demonstrated that HPPH-mediated PDT is an effective treatment option for superficial cancers such as skin and head and neck lesions in the oral cavity. [4][5][6][7][8] The efficacy of PDT is largely dependent on the spatial distribution and temporal changes of the photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] With high tumor avidity, the chlorin-based compound 2-(1-hexyloxyethyl)-2-devinyl pyropheophorbide-a (HPPH) has been shown to be a potential photosenstizer for imaging and treatment. 4 Recent HPPH-oriented laboratory research and early-phase clinical studies at Roswell Park Cancer Institute (RPCI) have demonstrated that HPPH-mediated PDT is an effective treatment option for superficial cancers such as skin and head and neck lesions in the oral cavity. [4][5][6][7][8] The efficacy of PDT is largely dependent on the spatial distribution and temporal changes of the photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of molecular oxygen in its ground triplet state ( 3 O 2 ) with 3 PS* generates a more reactive form of oxygen, i.e., singlet oxygen ( 1 O 2 ). This nonradical species is highly reactive toward electron-rich substrates such as aromatic rings, amines, and thioesters [8]. The contribution of both Type I and Type II reactions to cell death depends on several factors including, among others, the PS itself, the subcellular localization, the substrate, and molecular oxygen concentration within the target cells.…”
Section: Photodynamic Therapy As Antimicrobial Strategy: How It Workmentioning
confidence: 99%
“…Since Dougherty [8] in the 1970s began clinical trials for photodynamic destruction of cutaneous and subcutaneous malignancies, PDT has been used to treat esophageal [9], laryngeal, endobronchial, gastrointestinal, genitourinary, nervous, head and neck [10], oral leucoplakia, and skin malignancies [11].…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%
“…It has been described that tumor destruction of PDT is connected with indirect effects of PDT: blood vessel occlusion within vascularized tumors. These effects demonstrated [9] that PDT induces apoptosis and vascular endothelial damage [13,14]. It has also been mediated by the release of prostaglandin E2 (PGE2) and cytokines (IL-2, IL-1, TNF).…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%